Simplified Variable Node Unit Architecture for Nonbinary LDPC Decoder - Pham, Huyen Thi; Dao, Hung Tuan; Pham, Nghia Xuan (Journal of Science and Technology on Information security, 2020)
Abstract— Nonbinary low-density-parity-check (NB-LDPC) code outperforms their binary counterpart in terms of error correcting performance and error-floor property when the code length is moderate. However, the drawback of NB-LDPC decoders is high complexity and the complexity increases considerably when increasing the Galois-field order. In this paper, a simplified basic-set trellis min-max (sBS-TMM) algorithm that is especially efficient for high-order Galois Fields, is proposed for the variable node processing to reduce the complexity of the variable node unit (VNU) as well as the whole decoder. The decoder architecture corresponding to the proposed algorithm is designed for the (837, 726) NB-LDPC code over GF(32). The implementation results using 90-nm CMOS technology show that the proposed decoder architecture reduces the gate count by 21.35% and 9.4% with almost similar error-correcting performance, compared to the up-to-date works. Tóm tắt— Các mã LDPC phi nhị phân (NB-LDPC) vượt trội so với các mã LDPC nhị phân về chất lượng sửa lỗi và thuộc tính lỗi san bằng khi chiều dài là trung bình. Tuy nhiên, nhược điểm của các bộ giải mã NB-LDPC là tính phức tạp cao và độ phức tạp tăng đáng kể khi bậc của trường Galois cao. Trong bài báo này, thuật toán Trellis Min-Max dựa trên tập cơ sở được đơn giản hóa được đề xuất cho xử lý nốt biến mà hiệu quả cho các trường Galois bậc cao để giảm độ phức tạp của khối nốt biến (VNU) cũng như cả bộ giải mã. Kiến trúc bộ giải mã tương ứng với thuật toán đề xuất được thiết kế cho mã NB-LDPC (837, 726) thông qua trường GF(32). Các kết quả thực hiện sử dụng công nghệ CMOS 90-nm chỉ ra rằng kiến trúc bộ giải mã được đề xuất giảm số lượng cổng logic 21,35% và 9,4% với chất lượng sửa lỗi gần như không thay đổi so với các nghiên cứu gần đây.